Проблеми та перспективи давньоруської та середньовічної біоархеології - Козак, О.Д. (Археологія і давня історія України, 2010)
У статті наводяться короткі результати комплексного дослідження декількох різних в антропологічному і палеопатологічному сенсі давньоруських міських могильників. На їх основі виділено декілька комплексів ознак, що дозволяють характеризувати населення в його екологічному і соціальному оточенні. Автором описана методика дослідження кісткових решток із звичайних і масових поховань, а також можливості інтерпретації даних, отриманих в ході їх вивчення. В статье приводятся краткие результаты комплексного исследования нескольких различных в антропологическом и палеопатологическом смысле древнерусских городских могильников. На их основе выделено несколько комплексов признаков, позволяющих характеризовать население в его экологическом и социальном окружении. Автором описана методика исследования костных останков из обычных и массовых погребений, а также возможности интерпретации данных, полученных в ходе их изучения. Анализируются основные проблемы интерпретаций распределения в популяциях палеопатологических признаков и возможные пути их решения. Ставятся новые задачи в развитии данного направления науки. Today, the science of anthropology in Ukraine, especially medievistic, develops not only in the direction of ethnical anthropology. The leading projects that are being planned and developed in the old rus’ and medieval bioarchaeology are: researches of the physical type, demographic features, city and town population health; social stratification of the village-city disease and death rate and research of the consequences of social catastrophes — wars and epidemics. Methods and practices borrowed from european and russian archaeologists, as well as developed by us, are used for the best possible reconstruction of anthropological and paleoecological population traits. Short results of the complex research of a few old rus’ city burial grounds that differ in anthropological and paleopathological senses are displayed in the article. These researches have led to singling out multiple traits that allow us to characterise the population in its ecological and social background. The Author describes methods for researching bone remains from single and mass burials, and possibilities for interpretating the results of those researches. Also, fundamental problems with interpretation of distribution of the paleopathological features in the populace and their possible solutions are being analysed. New goals are set for future developement of this direction of science.